1996
DOI: 10.1021/bi952466d
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure and Backbone Dynamics of Recombinant Cucurbita maxima Trypsin Inhibitor-V Determined by NMR Spectroscopy,

Abstract: The solution structure of recombinant Cucurbita maxima trypsin inhibitor-V (rCMTI-V), whose N-terminal is unacetylated and carries an extra glycine residue, was determined by means of two-dimensional (2D) homo and 3D hetero NMR experiments in combination with a distance geometry and simulated annealing algorithm. A total of 927 interproton distances and 123 torsion angle constraints were utilized to generate 18 structures. The root mean squared deviation (RMSD) of the mean structure is 0.53 A for main-chain at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
56
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(64 citation statements)
references
References 46 publications
8
56
0
Order By: Relevance
“…Therefore, we use the structures of intact and modified forms of the natural protein (CMTI-I; Bode et al, 1989;Holak et al, 1989a;Krishnamoorthi et al, 1992aKrishnamoorthi et al, , 1992b for the recombinant versions as well. It was observed previously that the extra N-terminal Gly residue did not affect the structures of rCMTI-V (Liu et al, 1996a) and rCMTI-V* (Liu et al, 1996b). The entire molecule of rCMTI-III* appears to have undergone tertiary structural changes, as evidenced by 'H, "N, and "C chemical-shift changes of its backbone and side-chain atoms (Krishnamoorthi et al, 1992a(Krishnamoorthi et al, , 1992b(Krishnamoorthi et al, .…”
Section: Resultsmentioning
confidence: 66%
See 4 more Smart Citations
“…Therefore, we use the structures of intact and modified forms of the natural protein (CMTI-I; Bode et al, 1989;Holak et al, 1989a;Krishnamoorthi et al, 1992aKrishnamoorthi et al, , 1992b for the recombinant versions as well. It was observed previously that the extra N-terminal Gly residue did not affect the structures of rCMTI-V (Liu et al, 1996a) and rCMTI-V* (Liu et al, 1996b). The entire molecule of rCMTI-III* appears to have undergone tertiary structural changes, as evidenced by 'H, "N, and "C chemical-shift changes of its backbone and side-chain atoms (Krishnamoorthi et al, 1992a(Krishnamoorthi et al, , 1992b(Krishnamoorthi et al, .…”
Section: Resultsmentioning
confidence: 66%
“…Dynamical studies of rCMTI-V and rCMTI-V* (Liu et al, 1996a(Liu et al, , 1996b have shown that the newly formed C terminal (P, segment) in rCMTI-V* becomes more flexible, whereas the newly formed N terminal (PL fragment) remains as rigid as in the intact form. The reduced binding affinity of CMTI-V* relative to that of CMTI-V (Khyd = K:/Kd 9) may be attributed to the increased flexibility of the binding loop fragment, because the other regions of the inhibitor do not undergo any significant structural or dynamical changes.…”
Section: Internal Mobility and Protein Functionmentioning
confidence: 99%
See 3 more Smart Citations